Optimization of Growth and Yield of Several Varieties of Green Beans (Vigna Radiata L) Using Solid Oil Palm Waste on Red Yellow Podzolic Soil in Bengkulu - Rita Hayati; Jafrizal; Yukiman Armadi; Neti Kesumawati; Usman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to evaluate the effects of solid oil palm waste application and mung bean (Vigna radiata L.) varietal differences on growth and yield performance in red-yellow podzolic soils in Bengkulu, Indonesia. A factorial experiment was conducted using a Randomized Block Design (RBD) with three replications. The two factors tested were four levels of solid waste application (0, 10, 15, and 20 tons/ha) and three mung bean varieties (Vima 2, Vima 4, and Vima 5). Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that solid waste application significantly improved plant height, number of pods per plant, pod weight, and seed weight per plant. Variety also had a significant effect on plant height at 56 days after planting. No significant interaction was observed between the two factors. Overall, the application of 20 tons/ha of solid waste resulted in the highest improvements in agronomic parameters. Among the tested varieties, Vima 5 demonstrated the best overall performance. These findings suggest that using solid oil palm waste at an optimal dose can enhance mung bean productivity in red-yellow podzolic soils, supporting sustainable agricultural practices.